Emerging drugs for graft-versus-host disease. (2nd April 2016) - Kekre, Natasha; Antin, Joseph H.
ABSTRACT: Introduction : Graft-versus-host disease (GVHD) leads to significant morbidity and mortality after allogeneic stem cell transplantation. While corticosteroids alone are adequate in some cases, they are often insufficient, leading to poor quality of life associated with the symptoms of disease, or mortality from infection and GVHD. Moreover, corticosteroids have significant side effects and often do not lead to durable responses. New therapies are needed to improve the development and progression of acute and chronic GVHD. Areas covered : We discuss the spectrum of emerging drugs for GVHD prevention and therapy. Cellular therapies will be briefly discussed. The available pre-clinical and clinical data regarding monoclonal antibodies, interleukin-2, alpha-1 antitrypsin, histone deacetylase inhibitors, tyrosine kinase inhibitors, and proteasome inhibitors will be reviewed. Expert opinion : Although therapies emerging for GVHD remain promising, most of these drugs are still in early phase clinical trials and require randomized comparisons before formal conclusions can be drawn. It is likely that in the near future some of these agents will show improvements in response when compared with corticosteroids alone. Although it is difficult to predict which of these agents will be most promising, alpha-1 antitrypsin, ruxolitinib and interleukin-2 have demonstrated encouraging results.